Practical calibrations for a real-time digital omnidirectional camera - Nanda, Harsh; Cutler, Ross (CVPR, 2001)
Newly available high quality inexpensive digital 1394 cameras enable cheap and easy construction of omnidirectional cameras. We address several important issues for creating real-time panoramas, including user-assisted focusing, devignetting, and computer controlled brightness, contrast, and white balance. We demonstrate remarkable improvements in panoramic image quality using methods requiring very little CPU usage.